Breastfeeding and childhood obesity in the Azores - Ferreira, Ana Vaz (2021)
Background. The hypothesis that breasteeding has a protectve eﬀect in childhood obesity is not new; however, controversial results have been published. Since the Azores reported the lowest rate of breasteeding in Portugal and a high prevalence of childhood obesity, it becomes important to understand whether these facts are related or not. Objectves. To investgate the relatonship between breasteeding and childhood obesity in a populaton of Azorean children. Material and methods. A cross-sectonal study was carried out on 183 Azorean children between 5–10 years of age between September and December 2016. The weight and height of the children were measured at the consultaton and other variables were investgated through a questonnaire. The associaton between breasteeding and childhood obesity was tested using logistc regression models. Results. 18.6% of the children were obese and 74.3% were breasted. The exclusive breasteeding rate at 6 months was 3.3%. Complementary breasteeding was present in 39.3% at 6 months and 7.1% at 2 years. Obese children were breasted less tme than non-obesechildren, suggestng a dose-eﬀect relatonship (p = 0.025). We found a signifcant and independent relatonship between infant obesity and total tme of breasteeding (RR = 0.906; 95% CI [0.842, 0.974]; p = 0.008), physical actvity (RR = 0.883; 95% CI [0.801, 0.972]; p = 0.012) and maternal nutritonal status (RR = 3.452; 95% CI [1.361, 8.755]; p = 0.009). Conclusions. Breasteeding and physical actvity behaved as protectve factors for childhood obesity, while the nutritonal status of the mother acted as a risk factor. Childhood obesity is a current problem in the Azores, and breasteeding can be an eﬀectve, simple and aﬀordable tool to reduce this.